2004
DOI: 10.1194/jlr.m300431-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein A-II regulates HDL stability and affects hepatic lipase association and activity

Abstract: The effect of apolipoprotein A-II (apoA-II) on the structure and stability of HDL has been investigated in reconstituted HDL particles. Purified human apoA-II was incorporated into sonicated, spherical LpA-I particles containing apoA-I, phospholipids, and various amounts of triacylglycerol (TG), diacylglycerol (DG), and/or free cholesterol. Although the addition of PC to apoA-I reduces the thermodynamic stability (free energy of denaturation) of its ␣ -helices, PC has the opposite effect on apoA-II and signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
65
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 43 publications
3
65
0
2
Order By: Relevance
“…Finally, hepatic lipase activity is regulated by its binding to HDL. Tighter binding of hepatic lipase to apolipoprotein A-II containing HDL particles renders it inactive (29).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, hepatic lipase activity is regulated by its binding to HDL. Tighter binding of hepatic lipase to apolipoprotein A-II containing HDL particles renders it inactive (29).…”
Section: Discussionmentioning
confidence: 99%
“…The physiological role of apoA-II remains unclear. Experimental data indicate that apoA-II is likely to maintain the plasma HDL pool and enhance HDL stability by inhibiting hepatic lipase activity and CETP-mediated dissociation of lipid-poor apoA-I (17,18). It has been also shown that the rate of apoA-II production determines the distribution of apoA-I between HDL A-I and HDL A-I/A-II (19).…”
mentioning
confidence: 99%
“…It has previously been shown by several groups that the interaction between apoA-I and PON1 is important for stabilizing enzyme activity and improving specific activity (12,(25)(26)(27). ApoA-II, through its ability to stabilize HDL structure (8), may complement the stabilizing influence of apoA-I, if not present at excess levels. In contrast, apoA-II alone has a negative impact on PON1 activity (25).…”
Section: Discussionmentioning
confidence: 99%
“…Animal models have indicated that overexpression of apoA-II is detrimental for atherosclerosis (6,7), although the interpretation of such models is open to question. ApoA-II exhibits greater hydrophobicity than apoA-I, binds more tightly to lipids, and appears to stabilize the HDL complex (8). Its hydrophobic nature may be a factor in the influence of apoA-II on HDL-associated enzyme activity, by modulating interactions of enzymes with the lipoprotein.…”
mentioning
confidence: 99%